Post-Graduate Urology Training in Low- and Middle-Income Countries - Laith Baqain; Sanad Haddad; Ronny Baqain; Yaser El Hout; Mohammed Shahait (Société Internationale d’Urologie Journal)
Introduction: Urological conditions significantly impact global health, with increasing demand for urologists in both developed and developing countries. Disparities in access to surgical care between high-income countries (HICs) and low- and middle-income countries (LMICs) are evident. Despite advancements in urology, LMIC training programs often follow outdated curricula and traditional methods. Methodology: A comprehensive search strategy identified urology training programs in LMICs using the EduRank website, Google searches, and PubMed. Data were collected from the literature, official documents, and online resources, focusing on variables such as program duration, research requirements, and resident salaries. Results: The analysis revealed significant variability in program structures and requirements across LMICs. Residency training durations ranged from 4 to 6 years, with inconsistent research obligations and resident salaries averaging USD 12,857 annually, with a range from USD 5412 to USD 18,174. Fellowship opportunities were limited, with only a small number of programs achieving international accreditation. Conclusions: This study reveals disparities among urology training programs in LMICs, emphasizing the challenges faced by LMICs in providing comprehensive education. Outdated curricula, limited faculty, and insufficient resources contribute to the variability in training quality within LMICs. To bridge these gaps, there is a pressing need for standardized and locally tailored educational frameworks. Future research should focus on direct comparisons with programs in HICs to develop strategies that improve training opportunities and ensure equitable access to advanced urological education and care worldwide.